Daya Antibakteri Air Rebusan Bunga Rosella (Hibiscus sabdariffa Linn) dan Daun Teh Hitam (Camellia sinensis varian Assamica) Terhadap Penurunan Jumlah Koloni Bakteri Pada Sikat Gigi (Antibacterial Activity of Rosella Flower (Hibiscus sabdariffa Linn) a - Sisca Rizkia Arifianti; Dwi Warna Aju Fatmawati; Achmad Gunadi (Pustaka Kesehatan, 2016)
Background: Rosella flower and Black Tea Leaves is an herbal plant that contains antibacterial use full for decontamination materials toothbrush to prevent cross infection. Objective: The objective of this research was to identify the number of bacterial colonies on the water immersion results and more effective between the two materials. Method: This researchis an experimental laboratory by the posttest only control group design in 9 samples were divided into 3 groups (one control groups and the 2 treatments groups). Each group consisted of 3 samples. Decontamination method was by immersion toothbrush for 10 minutes. Result and Conclusion: The decline levels in the number of bacterial colonies on the toothbrush immersion is greatest in the Rosella group, decrease in the number of bacterial colonies after the immersion Rosella solution higher than Black Tea leaves, Rosella solution more effective as a material decontamination toothbrush. Keywords: toothbrush, Hibiscus sabdariffa, Camellia sinensis, bacterial colonies